A consumption timecycle: contextually situated and temporally recurring experiences. Issue 2 (24th August 2020) - Ryynänen, Toni; Heinonen, Visa
Abstract : Purpose: Temporal consumption experiences have been conceptualised as universal, subjective or practice-based experiences. Little research, though, addresses such experiences in conjunction with the repeated and situational consumption events that bring them about. The purpose of this paper is to extend current knowledge by examining how the temporal and situational intertwine during consumption events. For this purpose, the concept of a consumption timecycle based on the research data is constructed. Design/methodology/approach: The paper takes a longitudinal and researcher-led approach to study temporal consumption experiences. The data was collected through participant observations, video recordings and personal subjective introspections during three consecutive annual Nordic motorcycle consumer trade shows (2014–2016). The data was analysed using an interpretive approach. Findings: The results demonstrate five temporalities that characterise a consumption timecycle as follows: emerging, core, intensifying, fading and idle-time temporalities. The features of these temporal experiences are presented in the conclusions section of the paper. Research limitations/implications: Recalled temporal experiences are mediated experiences and they differ from lived experiences. The transferability or generalisability of the results might be limited, as the case is situated in the Nordic context. Originality/value: The paper presents the novel concept of a consumption timecycle that extends current debates about consumer time. The consumption timecycle is contrasted with established temporal concepts in consumer and marketing research.